100 WONDERS OF THE WORLD - HOFFMANN, Michael (Parragon Books Ltd, 2016)
The modern and fresh layout of '100 Wonders' uses excellent photography and a map for each entry to discover the most interesting and beautiful places in the world. Packed with facts, files, history, and stories covering natural wonders and stunning architecture from ancient times to present day.